Connectivity Dynamics in Dryland Litter Cycles: Moving Decomposition beyond Spatial Stasis. (10th July 2019) - Throop, Heather L; Belnap, Jayne
Abstract: Drylands (arid and semiarid ecosystems) cover nearly half of Earth's terrestrial surface, but biogeochemical pools and processes in these systems remain poorly understood. Litter can account for a substantial portion of carbon and nutrient pools in these systems, with litter decomposition exerting important controls over biogeochemical cycling. Dryland decomposition is typically treated as a spatially static process in which litter is retained and decomposed where it is initially deposited. Although this assumption is reasonable for mesic systems with continuous plant canopy cover and a stable subcanopy litter layer, dryland pools generally reflect discontinuous inputs from heterogeneous canopy cover followed by substantial litter transport. In the present article, we review horizontal and vertical transport processes that move litter from the initial deposition point and retention elements that influence litter accumulation patterns. Appreciation of the spatially dynamic litter cycle, including quantitative assessment of transport patterns, will improve estimates of the fate and distribution of organic matter in current and future drylands.